Early Aptian benthic foraminifera from El Cajón Formation, Huetamo, Michoacán (SW Mexico) - Lourdes Omaña-Pulido; Jerjes Pantoja-Alor (Revista Mexicana de Ciencias Geológicas)
The El Cajón Formation represents the second order highstand system tract of the Lower Cretaceous supersequence that affected the Huetamo region (SW Mexico). This formation contains a well preserved assemblage of shallow-water benthic foraminifera: Palorbitolina lenticularis (Blumenbach) Choffatella aff… in order to continue, download the full paper in PDF.